Comparing diatom diversity over three decades in the Brantas River, Malang, East Java, Indonesia - M Iqbal Najib Fahmi; Susriyati Mahanal; Siti Zubaidah; Ibrohim Ibrohim (Society for Indonesian Biodiversity, 2025)
Abstract. Fahmi MIN, Mahanal S, Zubaidah S, Ibrohim. 2025. Comparing diatom diversity over three decades in the Brantas River, Malang, East Java, Indonesia. Biodiversitas 26: 2519-2530. Diatoms are highly sensitive to environmental changes, making them reliable bioindicators. However, there is limited research on their long-term use in the Brantas River, Malang, Indonesia. This study aimed to compare the diatom diversity of the Brantas River, over three decades. This study was conducted at five observation stations during the dry season, and the results obtained from the comparison of species richness and diatom diversity index values revealed a significant downward trend at Stations II to V from the 1990s to the 2020s. Conversely, Station I exhibited relatively stable values for species richness and diatom diversity index. The results of the comparison of the density of genera and order for three decades showed the same results, with the genera Cocconies and the order Pennales being the most common species found. A meticulous examination of the prevalent species at the Station I consistently yielded analogous results over the course of three decades (Achnanthes lanceolata, Cocconeis placentula, and Nitzschia tryblionella). In contrast, Stations II to V exhibited fluctuations in the predominant species with each successive decade of observation. Based on the values of species richness, diversity index, and predominant species, it is suspected that there is a decrease in river water quality at Stations II to V from the 1990s to the 2020s, but not at Station I. This phenomenon may have been caused by environmental pollution and anthropogenic activities at Stations II-V. In contrast, Station I showed relatively the same water quality because it was located in a conservation area with minimal anthropogenic human activity. This study is limited to assessing water quality based on diatom diversity. Further research is needed to assess the physicochemical properties of the Brantas River in Malang.